Beginning funk bass - Laboriel, Abe. ([S.l.] : Star Licks, 1994)
Presents an essential foundation needed by every funk bass player.
Keywords: Laboriel, Abe -- Bass guitarist; Bass guitar -- Methods (Funk).; Funk (Music) -- Instruction and study; Funk (Music).